KEBUTUHAN BAHAN BAKU KAYU PADA INDUSTRI PENGOLAHAN KAYU FURNITUR (Studi Kasus PT. Rimba Mutiara Kusuma-Tanggerang) - Pusvitasari, Tia; Susdiyanti, Tun; Lidiawati, Ina (Jurnal Nusa Sylva, 2019)
Sustainability of wood supply is one of the important factors affecting the sustainability of the forestry industry that uses wood as its raw material. This study aims to determine how to manner supply the raw material needs as well as analyze the needs of the wood raw material and purchasing optimal wood raw material in PT Rimba Mutiara Kusuma. The method used in the research of interviews and observations where data are analyzed by qualitative  and needs wood raw material by regression analysis "time series" and the calculation of  purchasing optimal of raw materials with method Eqonomic Order Quantity uses quantitative analysis.The results showed that the need for raw materials in PT. Rimba Mutiara Kusuma done after a consumer orders a ordered product with raw material requirement calculations using formulas and recovery Comparing the nett volume of each product with predetermined recovery value is 45-50%. Recovery is the percentage that the company uses in calculating how cubication raw materials needed to produce each cubication finished product. The prediction results teak wood raw material requirements during the coming five years (2016-2020) obtained through analysis of time series prediction of 1089.65 m³ with an average volume of raw needs per year amounted to 217.93 m³ and predicted volume of raw material requirements mahogany of 1273,75 m³ with an average of 254,75 m³ every year. The optimal raw material purchase is 26.954 m³  teak and mahogany 27.86 m³ in every time order, the frequency 8 x with the cycle for 45 days.